THE EFFECT OF WORKING CAPITAL MANAGEMENT ON PROFITABILITY OF STATE-OWNED ENTERPRISE IN PROCESSING INDUSTRY SECTOR - Roni, Hamam; Djazuli, Atim; Djumahir, Djumahir (Jurnal Aplikasi Manajemen, 2018)
This study aims to examine the effect of various variables related to working capital management on profitability of state-owned enterprise in processing industry sector. The variables used in this research are profitability, cash turnover, receivable turnover, inventory turnover, liquidity, and asset structure. The population is entire state-owned enterprise of Indonesia in processing industry sector. The sampling technique used is purposive sampling technique. Based on the determined criteria, there are 13 companies as the sample. The data used are secondary data and research analysis tool is multiple linear regression. The results of this strudy indicate that inventory turnover and asset structure have significantly positive effect on corporate profitability. Nevertheless, Cash Turnover, Receivable Turnover, and Liquidity have no significant effect on the profitability on State -owned enterprise of indonesia in processing industry sector. For further research, it is advisable to add financial and non financial variables which are consideredmediate or moderate the effect of working capital management on profitability.